Exergaming in mixed reality for the rehabilitation of ataxic patients - Franzo', Michela; Pascucci, Simona; Serrao, Mariano; Marinozzi, Franco; Bini, Fabiano (2022 IEEE International Symposium on Medical Measurements and Applications (MeMeA), 2022)
Background: The purpose of a rehabilitation device is to generate tasks among cognitive difficulty stimulating the area of the cerebellum with no-automatics tasks when the situation is new to subject. An emerging technology, which overcomes these shortcomings, is the Mixed Reality. The aim of the study is to evaluate a possible updating of the prototype for rehabilitation of ataxic patients implementing exergame in Mixed Reality. Material and Methods: The version of the prototype based on Microsoft Kinect device and Arduino board with accelerometer/gyroscope sensor, presented in the previous congress, is compared with a reproduction of the same exergame in Mixed Reality environment with the HoloLens™ 2. The exergame consists in a pointing and reaching exercise to improve the control of upper limb during daily-life actions. Two subject performed the same exercise on the two different systems to investigate the differences between the systems. Results and Conclusion: The evaluation between the two systems was set up by analysing the differences between the subject's performances with the Kinect-based prototype and the HoloLens application: 3D trajectories and kinematics quantities. Despite of the restricted area of work, the high sample rate of HoloLens permits to follow much-unexpected patient's movements. The application of Mixed Reality for specific rehabilitation allows considering the requests of the therapists and the need of the patient to be always connected with the real world around him instead that in a total virtual space without real reference.